Steel H-Piles For A 11.7-Mile Long Rail Rapid Transit Project - Jeongbok Seo (Deep Foundations Institute, 2010)
The Dulles Corridor Metrorail Project (DCMP) involves the design and construction of a 23.1-mile extension of the Washington Metropolitan Area Transit Authority (WMATA) rail system. The initial 11.7-mile extension, with five transit stations and a new service and inspection yard, is to be constructed. The construction plan for the initial 11.7-mile extension includes installation of a total of an estimated 4,250 or 160,000 linear feet of driven 12x53 steel H-Piles at more than 80 different locations. At the time of this paper, approximately 40 percent of the piles have been installed and the remainder of piles will be installed by the end of 2010. This paper describes: 1) subsurface investigation program, 2) application of existing Codes and impact on the design of H-Pile, 3) design methods to determine geotechnical bearing capacity and pile tip elevation, 4) verification of capacity including PDA and Static Load Tests, 5) project specific pile load tests, and 6) QA/QC during pile driving.